PENGARUH PENDIDIKAN LINGKUNGAN HIDUP DAN IKLIM ORGANISASI SEKOLAH TERHADAP MOTIVASI BELAJAR IPS SISWA SMKN 1 MARTAPURA - Ananda Rosiana (Universitas Lambung Mangkurat, 2015)
The objectives of the research are: (1) to find out the influence of environment education towards IPS students' learning motivation at SMK 1 Martapura, (2) to find out the influence of the school organization climate towards IPS students' learning motivation at SMK 1 Martapura? (3) to find out the influence of both the environmental education and school organization climate simultaneously towards IPS students' learning motivation at SMK 1 Martapura. This research used survey method with quantitative research approach. The research samples were taken with proportion stratified random sampling technique of the population of 1,341 students, from which 308 students were obtained as samples. This research found that (1) the value of t count> t table (3.240> 1.971) means that the environment education partially affects IPS students' learning motivation, (2) the value of t count> t table (2.083> 1.971) means that the school organization climate partially affects IPS students' learning motivation, (3) F count> F table (7.488> 3.886) means that the environment education and climate of student organization simultaneously affect IPS students’ learning motivation, (4) based on the output, the obtained scores of Adjusted Square was 0.041 or (4.1%). Based on these results, it can be concluded that: (1) Environment education partially affected IPS students' learning motivation. The value of t count was positive. It means that the effect was positive. This means that the implementation of environment–based education, the motivation of IPS students at SMK 1 Martapura increased more, (2) School organization climate partially affected IPS students' learning motivation. The value of t count was positive. It means that the effect was positive. This means that the more comfortable the climate of the school organization, the more the increase of the motivation of IPS students at SMK 1 Martapura increase, (3) the environment education and the student organization climate simultaneously affected IPS students’ learning motivation.Keywords: environment education, school organization climate, learning motivation, social studies.